Feeding on fungi: genomic and proteomic analysis of the enzymatic machinery of bacteria decomposing fungal biomass. (31st August 2020) - Starke, Robert; Morais, Daniel; Větrovský, Tomáš; López Mondéjar, Ruben; Baldrian, Petr; Brabcová, Vendula
Summary: Dead fungal biomass is an abundant source of nutrition in both litter and soil of temperate forests largely decomposed by bacteria. Here, we have examined the utilization of dead fungal biomass by the five dominant bacteria isolated from the in situ decomposition of fungal mycelia using a multiOMIC approach. The genomes of the isolates encoded a broad suite of carbohydrate‐active enzymes, peptidases and transporters. In the extracellular proteome, only Ewingella americana expressed chitinases while the two Pseudomonas isolates attacked chitin by lytic chitin monooxygenase, deacetylation and deamination. Variovorax sp. expressed enzymes acting on the side‐chains of various glucans and the chitin backbone. Surprisingly, despite its genomic potential, Pedobacter sp. did not produce extracellular proteins to decompose fungal mycelia but presumably feeds on simple substrates. The ecological roles of the five individual strains exhibited complementary features for a fast and efficient decomposition of dead fungal biomass by the entire bacterial community.